Recreational fishing on the coastal hot spots of İzmir Inner Bay (Aegean Sea, Turkey) : socio-economics and management implications - Ulaş, Ali (Array, 2019)
In this study, we analyzed social and economic dimensions of shore-based recreational fishing (RF) along İzmir Inner Bay in the Metropolitan Province İzmir of Turkey. 634 shore-based recrea-tional fishers were interviewed via on-site face-to-face interviews during the fishing activity from January to December in 2016. Market value approach was utilized to calculate net economic values and expenses of recreational fishers along in eight coastal districts, Göztepe, Karataş, Konak, Pasa-port, Alsancak, Bayraklı, Karşıyaka and Bostanlı along the coast of the inner bay. The annual fish-ing efforts demonstrated significant differences among districts. For example; Bostanlı fishers that have higher education levels with higher income spent higher time for RF but, finally, this attitude of Bostanlı fishers resulted in low CPUE levels. Considering the RF experience of Bostanlı fishers, they are either not likely or able to target or catch bigger or more fish. In contrast, Göztepe fish-ers seems much professional compared to fishers by having the highest amount of catch in shortest time compared to rest of the districts. The highest mean CPUE was observed for Göztepe, Karataş and Konak fishers even so, these CPUE amounts were much under the ones determined in previous studies in Turkey. Considering the catch composition of fishers, S. auratus was the most common catch for all fishers. Secondly, D. labrax and Mugilid species constituted the majority. High fishing related expenditures were observed in all districts, then harvesting values reached quite high levels considering the previous studies. To conclude, RF in İzmir Inner Bay of Turkey is great social and economic activity by generating increase in RF related expenditures, jobs and indirect economic activity in services sector. The results of this study provide an update information of the recreational fishers’ profile to help regulate recreational fishery.